Association between malnutrition and leucopenia in patients with osteosarcoma - Wu, Haixiao; Li, Shu; Lin, Yile; Wang, Jun; Chekhonin, Vladimir P.; Peltzer, Karl; Baklaushev, Vladimir P.; Abbas, Kirellos Said; Zhang, Jin; Li, Huiyang; Zhang, Chao (Frontiers in Nutrition, 2022)
Background & Aim: Leucopenia (LP) greatly limits the efficacy of chemotherapy in osteosarcoma patients. This study aimed to evaluate the nutritional status of osteosarcoma patients before chemotherapy, assess the risk of LP during the perichemotherapy period, and explore the association between the two. Materials and methods: This study retrospectively analysed osteosarcoma patients treated in the Tianjin Medical University Cancer Institute and Hospital, China, between January 2009 and December 2020 according to the inclusion and exclusion criteria. Malnutrition in adolescents (5 to 19 years old) and adults (≥ 20 years old) was diagnosed using WHO AnthroPlus software (version 1.0.4) and Global Leadership initiative on Malnutrition (GLIM), respectively. According to the diagnostic criteria of LP in CTCAE 5.0, patients were divided into the LP group and the non-LP group. Results: A total of 245 osteosarcoma patients were included. The incidence of malnutrition was 49.0%, and the incidence of LP was 51.8%. The incidence of malnutrition in adolescent patients was 53.1%, and their incidence of LP was 55.2%; the incidence of malnutrition in adult patients was 43.1%, and their incidence of LP was 47.1%. Logistic regression analysis showed that malnutrition before chemotherapy was an independent risk factor for the occurrence of LP after chemotherapy (OR=6.85, CI=2.16-25.43; and OR=35.03, CI=6.98-238.46 in mildly and severely malnourished young patients; OR=6.06；CI=1.43-30.16; and OR=38.09, CI=7.23-285.78 in mildly and severely malnourished adult patients, respectively). The results showed that age and nutritional status had a joint effect on the occurrence of LP. Conclusions: The nutrition status of osteosarcoma patients before chemotherapy is significantly correlated with the occurrence and severity of LP during peri-chemotherapy period. During osteosarcoma chemotherapy, necessary nutritional support should be given to patients of different ages to correct their malnutrition status in a timely manner, ultimately improving the efficacy of chemotherapy and the prognosis of patients.